Assembly of poly-3-(hexylthiophene) nanocrystals in marginal solvent: The role of PCBM. (December 2018) - Da Pian, Marta; Maggini, Michele; Vancso, G. Julius; Causin, Valerio; Benetti, Edmondo M.
Graphical abstract: Highlights: The morphological and photophysical properties of P3HT nanocrystals (NCs) are determined by the assembly conditions under marginal solvent environments. When PCBM is added to yield mixtures typically applied for fabricating organic photovoltaics (OPVs), the assembly/crystallization process results confined, while the formed P3HT NCs present more defects compared to those assembled from pure polymer suspensions. Abstract: Poly-3-(hexyl thiophene) (P3HT) represents the benchmark semiconducting polymer for the fabrication of organic photovoltaics (OPVs), where it acts as electron donor component in combination with [6, 6]-phenyl-C61-butyric acid methyl ester (PCBM), as electron acceptor counterpart. The assembly of P3HT under marginal solvent conditions to form dispersions of fibrillar nanocrystals (NCs) is a particularly attractive method for the subsequent fabrication of highly crystalline films, if compared to depositions involving polymer solutions followed by relatively harsh thermal/solvent treatments, which are often incompatible with sensitive substrates. However, the mechanisms that drive the assembly of P3HT to NCs in marginal solvents are not fully understood, while the effects induced by the presence of PCBM during polymer assembly are still debated. In order to shed light into these processes, we systematically investigated the aggregation/crystallization behaviour of P3HT to NCs under different marginal-solvent conditions and in the presence of different relative contents of PCBM. The starting concentration of P3HT was shown to influence assembly kinetics, the micro-/nano-morphology and the photophysical properties of the formed NCs, as demonstrated by combining atomic force microscopy (AFM) and UV–vis adsorption spectroscopy. Polymer assembly to NCs was also highly dependent on the relative concentration of PCBM, within P3HT:PCBM mixtures typically applied in OPVs. In particular, the combination of UV–vis, AFM and wide-angle X-ray scattering (WAXD) highlighted that PCBM confined the aggregation/crystallization process of P3HT NCs, allowing the formation of extended crystallites, while at high concentrations it hindered the formation of NCs slowing down their assembly.